MCDONALDISASI DAN DEHUMANISASI PEGAWAI RESTORAN CEPAT SAJI DI BALI - Setyoko, Tendi; Ranteallo, Ikma Citra; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT This Research use term of George Ritzer, that is McDonaldization and of dehumanization worker to perceive five branch of McDonald's in Bali. This Research have purpose to know all kind of dehumanization in interpretation worker of restaurant fast food McDonald's, what later, then exposed in the form of erudite study. Pursuant to result of descriptive research method qualitative observation and explanative in field, and also circumstantial interview to ten worker of McDonald's, writer find matters which is equal to found by Ritzer in the year 1993 ago, that is: efficiency, power of arithmetic, power of prediction, and technological control to worker to reach satisfaction of customer . Key words: McDonaldization, dehumanization, worker, technology.